Dinamics of efficiency of elevated green weight of ecosystems with a various level of anthropogenous loading - O. G. Nazarenko; V. D. Kumacheva (Юг России: экология, развитие)
The article shows the results of 4-years research of productivity of ecosystems with various level of anthropogenous influence. It is established that productivity, expressed in the sire of biomass is an informative index, providing with possibility to estimate both climatic conditions of steppe phytocenosis forming and level of anthropogenous influence.